Lucky [videorecording (DVD)] - Stanton, Harry Dean, 1926-2017; Lynch, David, 1946-; Livingston, Ron; Begley, Ed, Jr; Skerritt, Tom (Magnolia Home Entertainment, 2018)
The spiritual journey of a ninety year old atheist, and the quirky characters that inhabit his off-the-map desert town.